Children's Interpretations of Numerically Quantified Expression Ambiguities: Evidence from Quantified Noun Phrases and Bare Cardinals - Marilena Mousoulidou; Kevin B. Paterson (MDPI AG, 2024)
Understanding how children comprehend text by forming links between sentences has been the focus of research for decades. Such research has consistently shown that children use anaphors and resolve ambiguities in a different manner than adults. The present study examined a less-studied anaphoric reference that arises when two numerically quantified expressions (e.g., "three cats... two cats...") are used in the text. Focusing on 249 six- to eight-year-old children and 50 adults for comparison, the study employed a picture selection task across six experiments to assess interpretative preferences in ambiguous and unambiguous discourses containing numerically quantified expressions. The findings indicate a pronounced difference in interpretative strategies: unlike adults, who predominantly adopted an anaphoric subset reading, children showed a consistent preference for the non-anaphoric reading, even in contexts explicitly disambiguated towards this interpretation. This preference persisted across various experimental manipulations, highlighting challenges in text integration and comprehension among children. Contributing to the developmental trajectory of language comprehension, this study underscores the complexity of cognitive development and linguistic interpretation, revealing significant developmental differences in processing numerically quantified expressions and anaphoric references within discourse.